2018
DOI: 10.1177/1074248417753677
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces Plasma Inflammatory and Oxidant Biomarkers in Patients With Risk of Atherosclerotic Cardiovascular Disease

Abstract: Key markers of oxidative stress/inflammation such as CRP, ET-1, total nitrite, and MPO are associated with an increased risk of ASCVD. Moderate- and high-intensity atorvastatin use reduces plasma oxidative stress and inflammation regardless of ASCVD risk and independent of its lipid-lowering effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A total of 1970 were excluded (duplicates or irrelevant). After reviewing the remaining 18 articles, 3 were further excluded, leaving 15, reporting 17 treatment arms in 773 patients (mean age of 53 years, 54% males), for final analysis ( Figure 1 and Table 1 ) [ 27 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1970 were excluded (duplicates or irrelevant). After reviewing the remaining 18 articles, 3 were further excluded, leaving 15, reporting 17 treatment arms in 773 patients (mean age of 53 years, 54% males), for final analysis ( Figure 1 and Table 1 ) [ 27 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endothelin-1 (ET-1) is a potent vasoconstrictor and inflammatory factor that is produced by endothelial cells, fibroblasts and cardiac myocytes [36]. We have shown that patients with history of recent MI have increased plasma levels of ET-1 and increased risk of atherosclerotic cardiovascular events indicating a link to endothelial dysfunction [37, 38]. Furthermore, patients with hyperthyroidism have increased levels of plasma ET1 and this increase is associated with increased risk of atrial fibrillation [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies examined plasma levels within days of commencing therapy. The significant decline at day 7 noted in Group 3 of the current study, and associated fall in hsCRP presumably relates to reduced inflammation post ictus 32,33 . Values after 7 days remained unchanged despite a further fall in hsCRP suggesting that only severe inflammation affects ET-1 expression and circulating levels in this age group.…”
Section: Discussionmentioning
confidence: 45%